Community services in Indonesia regarding waste handling and management: Mapping and bibliometric analysis - Dave Mangindaan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Indonesia is a country with large area of land and sea, and therefore possesses vast amount of natural resources. However, the use of natural resources without proper handling or management of the waste causes a serious problem in Indonesia. Besides the lack of waste management facilities, local communities also exhibit insufficient awareness and knowledge in waste management. From the point of view of universities and higher education institutions, this issue might be resulted from few community development or community service, as well as lack of knowledge dissemination. In order to equalize the knowledge of the local communities with that of people of the large cities, then Indonesian universities perform community service (a part of the university tridarmas). With the intention to obtain effective and efficient community service, in this manuscript we describe mapping of publication of community service in the Scopus (a trusted database of international publication) in the field of waste management. From 2410 data from Scopus, they are sorted to obtain 38 publications related to the community service and community development for the waste management. The locations of the community services are mapped, as distributed in islands of Sumatera, Java, Bali, Kalimantan, Sulawesi, and Papua. From the mapping, it can be observed that most of the published community service activities are concentrated in Java, Bali, and some at Sulawesi. It is therefore imperative to have future explorations at Kalimantan, Sumatera, and Papua. The published community services in Scopus commonly discuss about the developments of (1) recycling or upcycling, (2) socioeconomic evaluation, (3) performance evaluation, and (4) ecological evaluation of the waste management. Besides the mapping, bibliometric analysis is also performed where it is shown that the community service related to the waste management in Indonesia is highly tied with the sustainable development, rural areas, waste or wastewater treatment, sanitation, etc. where all these issues are important and urgent to obtain economic equality (especially for people of Kalimantan, Sumatera, and Papua) to achieve Gold Indonesia 2045.